High prevalence of low back pain in college rifle athletes - Urbach, B.; Mansfield, C.; Harr, M.; Briggs, M. S.; Onate, J.; Boucher, L. (International Journal of Sports Physical Therapy, 2025)
Background The sport of rifle places unique physical demands on its athletes relative to other collegiate sports, including maintaining lumbar-straining positions for extended time. Anecdotal reports of low back pain (LBP) are common among collegiate rifle athletes, but the prevalence of LBP in this population has not yet been established in the literature.